Karakterisasi Morfologi dan Anatomi Stroberi (Fragaria x ananassa D. cv. Festival) Hasil Induksi Kolkisin - Ana Susianti; Ganies Riza Aristya; Sutikno S; Rina Sri Kasiamdari (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2015)
Strawberry is a plant cultivated in subtropical countries, while Indonesia’s tropical climate. This is not accordance with the conditional of the natural growth of strawberries. Strawberries cultivar Festival is one of holticulture products in society. The high rates of consumption of strawberries are not equal with production and quality of strawberries. The quality of strawberries were determined by fruit size and uniformity of fruit. Effort that can be used to improve the qualityof strawberry production is polyploiditation with mutagenic substance, example colchicine. Result of polyploidy in morphological character are bigger. Technique of polyploidy with colchicine will be success if the number and structure of chromosom in cell nucleus are changes. Chromosome number changes will be change to anatomy, morphology and physiology plants. The aims of this research were to know the differences of anatomical and morphological characters of strawberry cultivar Festival after colchicine induction and find out the influence of the colchicine concentration differences in morphological and anatomical character of strawberry cultivars Festival. The research was have two main stages. The first were observation and scoring of 25 morphological characters of strawberries after colchicine induction with 0%; 0,01% and 0,05%. The second, preparations with paraffin method on the root, steam, leaves and fruit of the strawberry plant after colchicine induction. The observation of anatomical characters are measurements number cell was from of the root, steam, leaves and fruits. The results showed that induction of colchicine in strawberry cultivars festival showed different morphological characters on the density of the leaves, number of stems, fruit ripening time, fruit size, fruit sweetness of the outer color of the fruit, fruit acidity compared to control plants. Anatomical characters of cell size increases the cortex and pith of stems, leaves, cell mesofil cells of the cortex and pith of fruit. Colchicine induction of 0.05% was more effective in increasing the size of the fruit while the induction of colchicine of 0.01% was more effective at increasing the size of vegetative organs of strawberry cultivars Festival plants.Keywords: anatomy, colchicine, Festival Cultivars, morphology, strawberry